Assessing thermodynamic parameter sensitivity for simulating temperature responses of soil nitrification. Issue 9 (15th August 2019) - Mukhtar, Hussnain; Lin, Yu-Pin; Lin, Chiao-Ming; Petway, Joy R.
Abstract : The sensitivity of SQRT model-estimated parameters varied over a temperature gradient whereas no variation in MMRT model-estimated parameters, in simulating temperature responses of soil nitrification over the temperature range, was observed. Abstract : Soil nitrification responses to temperature have major implications for the global nitrogen cycle. Temperature sensitivity of soil nitrification has been modeled using several mathematical models, yet the extent to which model-generated thermodynamic parameters are accurate and sensitive in describing temperature sensitivity is unclear. In this study, we performed global sensitivity analysis to identify the key thermodynamic parameters that are most influential when simulating the temperature response of the soil nitrification potential (NP) across two different temperature gradients (4–40 °C and 20–45 °C) which are imposed upon sixteen different soils with square root growth (SQRT) and macromolecular rate theory (MMRT) models. We found that two thermodynamic parameters stand out as moderately to highly sensitive, and are uniquely identifiable in each model, regardless of the temperature range. The minimum and maximum measured temperatures seem to have no impact on the list of sensitive parameters but do influence the parameter ranges, especially for the SQRT model. However, parameters that control the minimum temperature and curvature of the NP response curve ( T min and Δ C ‡P) were found to have little to no sensitivity to SQRT and MMRT model outputs, respectively. We show that the parameter sensitivity and range of measured temperatures influence the complementary model's ability to describe the temperature sensitivity of soil nitrification. Our proposed framework enhances the accurate interpretation of existing thermodynamic parameters that explain the temperature sensitivity of soil biochemical processes, and provides methodological recommendations for future temperature sensitivity studies.